Essential Minerals of Rice in West Java Indonesia and Its Daily Intake Estimation - W.Y.N. Syahfitri; E. Damastuti; N. Adventini; D.P.D. Atmodjo; I. Kusmartini; S. Kurniawati; D.D. Lestiani; M. Santoso (Atom Indonesia, 2018)
Rice (Oryza sativa L.) is the staple food for more than half of the world’s population and a major source of essential minerals. Essential minerals such as cobalt (Co), chromium (Cr), iron (Fe), selenium (Se), and zinc (Zn) play an important role in metabolism and physiological function. Information of rice micronutrient and its content quality in Indonesia is limited; however, its availability is important for estimating the daily intake of the nutrients and its contribution tothe Recommended Dietary Allowance (RDA). The research aimed to determine the micronutrient content in rice from twelve regions in West Java by means of neutron activation analysis (NAA) and estimate the nutrient intake from rice. The samples were irradiated with thermal neutron flux of 1013n/(cm2 s) at the rabbit system facilites of the G.A. Siwabessymultipurpose reactor, then counted using a HPGe detector. The contents of Co, Cr, Fe, Se, and Zn in rice were found to be in the ranges of0.003 to 0.220, ≤0.001-0.679, ≤0.060-18.36, ≤0.020-0.975, and 8.558-28.83 mg/kg respectively. The daily intakes of Co and Cr were found generally sufficient, while Fe, Se, and Zn intakes were significantly less than the RDA in almost all regions observed. The exception was found for Se intake in Garut which exceeded its RDA. It can be concluded that rice is the main contributor of essential minerals intake; however, for nutritional fulfillment of human body, a balanced varied diet should be taken into consideration